2014
DOI: 10.1002/jts.21884
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Child PTSD Symptom Scale in Latino Children

Abstract: The Child PTSD Symptom Scale (Foa, Johnson, Feeny, & Treadwell, ) is a self-report measure of posttraumatic stress disorder symptoms (PTSD) in children and adolescents. Despite widespread use of this measure, no study to our knowledge has examined its psychometric properties in Latino children. This study examined the factor structure, internal consistency, and convergent validity of the measure utilizing a sample of 161 Latino students (M = 11.42 years, SD = 0.70) at high risk of exposure to community violenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
4
12
0
Order By: Relevance
“…The Child PTSD Symptom Scale (CPSS; utilized in Samples 1, 2, and 4), available in English (Foa, Johnson, Feeny, & Treadwell, ) and Spanish (Kataoka et al., ), is a child self‐report checklist of symptoms of posttraumatic stress disorder (PTSD; 17 items) and related impairment (7 items). The English and Spanish versions have shown excellent internal consistency (α from .88 to .89 in current samples), test‐retest reliability, and convergent validity with other measures of traumatic stress (Foa et al., ; Gudiño & Rindlaub, ).…”
Section: Methodsmentioning
confidence: 66%
“…The Child PTSD Symptom Scale (CPSS; utilized in Samples 1, 2, and 4), available in English (Foa, Johnson, Feeny, & Treadwell, ) and Spanish (Kataoka et al., ), is a child self‐report checklist of symptoms of posttraumatic stress disorder (PTSD; 17 items) and related impairment (7 items). The English and Spanish versions have shown excellent internal consistency (α from .88 to .89 in current samples), test‐retest reliability, and convergent validity with other measures of traumatic stress (Foa et al., ; Gudiño & Rindlaub, ).…”
Section: Methodsmentioning
confidence: 66%
“…Seven subsequent items probe impairment with regard to saying prayers, doing chores, friendships, hobbies, schoolwork, family relationships, and general happiness. Reliability estimates for the English and Spanish version of the Child PTSD Symptoms Scale range from 0.91 to 0.92 (Gudiño and Rindlaub, 2014) and sample-specific alpha coefficient included 0.90, noting excellent internal consistency.…”
Section: Methodsmentioning
confidence: 99%
“…The CPSS has been used in research and clinical settings across various populations both in high-income and low-and middle-income countries. Studies across the US have found the CPSS to have strong validity and reliability [34]. The Cronbach's alpha in the current study is  = .933.…”
Section: Measures For Children Of Female Entertainment Workersmentioning
confidence: 52%